2010
DOI: 10.21273/jashs.135.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluations of the Cry1Ia1 Protein Found in the Transgenic Potato ‘SpuntaG2’

Abstract: The transgenic potato ‘SpuntaG2’ (Solanum tuberosum), which is resistant to potato tuber moth (Phthorimaea operculella), was subjected to protein safety evaluations including protein equivalency tests for the Cry1Ia1 protein from ‘SpuntaG2’ and bacterially produced Cry1Ia1, toxicity and allergenicity evaluations of Cry1Ia1 protein, and compositional equivalency of ‘SpuntaG2’ compared with non-transgenic ‘Spunta’. Western blot analysis and biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Based on multiple years of field, storage, and agronomic trials, as well as measurement of agronomic traits, it was concluded that 'SpuntaG2' gave complete resistance to potato tuber moth infestation in the field and in storage and that it does not differ from non-transgenic 'Spunta' with respect to yield, other important agronomic properties, tuber quality, and processing traits. Furthermore, two companion articles (Quemada et al, 2010;Zarka et al, 2010) give a complete characterization of 'SpuntaG2' at the molecular level and a thorough protein safety evaluation that demonstrated that 'SpuntaG2' is safe for human consumption. Therefore, in South Africa where potato tuber moth is a serious pest of potatoes, 'SpuntaG2' could provide growers with an alternative to the variable results achieved with approved chemical insecticides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on multiple years of field, storage, and agronomic trials, as well as measurement of agronomic traits, it was concluded that 'SpuntaG2' gave complete resistance to potato tuber moth infestation in the field and in storage and that it does not differ from non-transgenic 'Spunta' with respect to yield, other important agronomic properties, tuber quality, and processing traits. Furthermore, two companion articles (Quemada et al, 2010;Zarka et al, 2010) give a complete characterization of 'SpuntaG2' at the molecular level and a thorough protein safety evaluation that demonstrated that 'SpuntaG2' is safe for human consumption. Therefore, in South Africa where potato tuber moth is a serious pest of potatoes, 'SpuntaG2' could provide growers with an alternative to the variable results achieved with approved chemical insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…'SpuntaG2' is a transgenic potato cultivar containing the cry1Ia1 gene from Bacillus thuringiensis for resistance to potato tuber moth. This cultivar has been characterized at the molecular level (Zarka et al, 2010) and has been thoroughly evaluated for safety as a human food source (Quemada et al, 2010). The current study focuses on the agronomic performance of 'SpuntaG2' and its efficacy against potato tuber moth in the field and in storage.…”
mentioning
confidence: 99%
“…Equivalency tests of Cry1Ia1 from GMO potato and E. coli produced Cry1Ia1 showed no difference in size in Western blot. 23 The Western blot results also showed that Cry2Aa2 expressed in tobacco leaves was larger than the E. coli expressed Cry2Aa2. 12 The larger molecular protein on lane 5 could be the cotton Cry1Ac protein precursor.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 88%
“…Western blot is widely used across a broad range of biological science disciplines as well as the detection of GMO proteins expression level, environmental fate or biosafety investigation. ,, Western blot provides useful information, like protein degradation, truncation, and modification after translation, which is not readily gathered from other immunoassays. After gel electrophoretic separation and protein transfer, a target protein is detected by a specific antibody, which confirms the identity of the target protein.…”
Section: Introductionmentioning
confidence: 99%
“…The research presented here is the first in a series of three articles including Quemada et al (2010) and Douches et al (2010) documenting the extensive research necessary to apply for the release of a GM potato ('SpuntaG2') in South Africa. This project was funded by the U.S. Agency for International Development (Washington, DC) and is a collaborative effort between Michigan State University Potato Breeding and Genetics Program (East Lansing) and the Agricultural Research Council, Vegetable and Ornamental Plant Institute [(ARC-VOPI), Pretoria, South Africa].…”
mentioning
confidence: 99%